2019
DOI: 10.1128/mbio.00839-19
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Intrinsic and Extrinsic Factors That Shape the Human Skin Microbiome

Abstract: Despite recognition that biogeography and individuality shape the function and composition of the human skin microbiome, we know little about how extrinsic and intrinsic host factors influence its composition. To explore the contributions of these factors to skin microbiome variation, we profiled the bacterial microbiomes of 495 North American subjects (ages, 9 to 78 years) at four skin surfaces plus the oral epithelium using 16S rRNA gene amplicon sequencing. We collected subject metadata, including host phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 53 publications
12
143
2
1
Order By: Relevance
“…In aging, we detected different species diversities and compositional characteristics of skin microbiomes in different age groups. These differences could be ascribed to continuous self-regulation and self-renewal of skin microbiomes, related to individual's residential environment and host selection pressures (e.g., local physiological status) (Kim et al, 2018;Dimitriu et al, 2019). Consistent with previous studies, higher species diversities of cutaneous bacterial communities were found with aging for both exposed and non-exposed sites (Leung et al, 2015(Leung et al, , 2016aShibagaki et al, 2017).…”
Section: Similar Microbial Variation Patterns In Intrinsic Skin Agingsupporting
confidence: 85%
“…In aging, we detected different species diversities and compositional characteristics of skin microbiomes in different age groups. These differences could be ascribed to continuous self-regulation and self-renewal of skin microbiomes, related to individual's residential environment and host selection pressures (e.g., local physiological status) (Kim et al, 2018;Dimitriu et al, 2019). Consistent with previous studies, higher species diversities of cutaneous bacterial communities were found with aging for both exposed and non-exposed sites (Leung et al, 2015(Leung et al, , 2016aShibagaki et al, 2017).…”
Section: Similar Microbial Variation Patterns In Intrinsic Skin Agingsupporting
confidence: 85%
“…has been identified as part of the healthy skin microbiome and Neisseria sp. is common in the mucosal surface of vertebrate hosts of I. ricinus (Elliott et al, 2005;Dimitriu et al, 2019). In contrast to the ovary, the midgut did not show a core microbiome, as we did not detect any common bacterial genera in all midgut samples.…”
Section: Discussioncontrasting
confidence: 53%
“…Genus Corynebacterium was highly abundant in first-generation members (Table S7c). Recent study understanding the extrinsic and intrinsic host factors influencing skin microbiome composition suggested that Corynebacterium OTUs were associated with skin aging 66 , specifically with the hyperpigmented spots and wrinkles 66 . With the increasing age, physiological changes occur in the skin structure explains the association of key bacterial taxa in the members of the respective age groups.…”
Section: Discussionmentioning
confidence: 99%